Food consumption and nutritional status of children at a Municipal School in Alfenas/Minas Gerais (MG) (Research, Society and Development, 2024)
Introduction: School plays a crucial role in promoting healthy eating habits during childhood, as problems such as extreme thinness and overweight/obesity are a concern in this age group. Objective: This study aims to evaluate the food consumption and nutritional status of children in a municipal school in Alfenas - Minas Gerais (MG). Methodology: Qualitative and quantitative research was carried out with children aged 8 to 10 years, involving anthropometric assessment, nutritional diagnosis and analysis of the school menu. Results: Of the 105 participants, the majority (65.71%) had adequate nutritional status. However, 4.76% are classified as thin, 14.30% are overweight and 15.23% are obese. The school menu, over five days, partially met the recommendations, with energy variations and deficiencies, especially in vitamin A. Conclusion: The study highlights the need to promote healthy eating habits at school and at home, as nutritional deficiencies can harm the development of children, hypovitaminosis A being an example, which can affect eye health, increase susceptibility to infections and affect the proper growth and development of children (WHO, S.D.).